Evaluation of factors leading to formation of price-bubbles in the real estate market of Lithuania - Dzikevičius, Audrius; Kazlauskas, Lukas; Bruzgė, Šarūnas (Business: Theory and Practice, 2015)
Recently, real estate market has been discussed more frequently in the framework of economic analysis. The global economic crisis of 2008 has demonstrated the severity of financial shock that can be caused by inconsiderate investments in the real estate market. The present article analyses business cycles and the phenomenon of a price-bubble in that context. Drawing on the analysis of reference literature we identify the main reasons that can lead to fluctuations of prices in the real estate market. Finally, drawing on correlation and regression analysis we determine which factors have the strongest influence on the Lithuanian real estate market.